2021
DOI: 10.1002/rsa.20993
|View full text |Cite
|
Sign up to set email alerts
|

The number of satisfying assignments of random 2‐SAT formulas

Abstract: We show that throughout the satisfiable phase the normalized number of satisfying assignments of a random 2-SAT formula converges in probability to an expression predicted by the cavity method from statistical physics. The proof is based on showing that the Belief Propagation algorithm renders the correct marginal probability that a variable is set to "true" under a uniformly random satisfying assignment. KEYWORDS 2-SAT, Belief Propagation, satisfiability problem 1 INTRODUCTION Background and motivationThe ran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Giráldez-Cru and Levy [21,22] propose a new model of random formulas that, besides heterogeneity, also consider the notion of locality in formulas. Achlioptas et al [23] computes the number of assignments of uniform random 2-SAT formulas, using the cavity method. Finally, Bläsius et al [24] analyze the hardness of random instances according to their heterogeneity and locality.…”
Section: Introductionmentioning
confidence: 99%
“…Giráldez-Cru and Levy [21,22] propose a new model of random formulas that, besides heterogeneity, also consider the notion of locality in formulas. Achlioptas et al [23] computes the number of assignments of uniform random 2-SAT formulas, using the cavity method. Finally, Bläsius et al [24] analyze the hardness of random instances according to their heterogeneity and locality.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that 1 n log Z(\Phi ) is concentrated around its expectation [1,16] for \alpha < (1 -o k (1)) \cdot 2 k ln k/k. However, for the random k-SAT model, there is no known formula for the expectation \BbbE 1 n log Z(\Phi ) (though see [3] and [40,17] for progress along these lines for the case k = 2 and for more symmetric models of random formulas, respectively). Regarding the algorithmic question, Montanari and Shah [36] have given an efficient algorithm to approximate a closely related (permissive) version 1 of 1 n log Z(\Phi ) if \alpha \leq 2 log k k (1 + o k (1)), based on the correlation decay method and the uniqueness threshold of the Gibbs distribution.…”
mentioning
confidence: 99%